Somatic Embryogenesis Detection in Carnivorous Plants - Kok, Andrew De Xian (2016)
Carnivorous plants are generally uncommon and some of the species are endangered. These plants have the most unusual adaption to survive in environment that is nutrient deficient by capturing preys. Hence, propagation is required to prevent the extinction of these species. In vitro propagation could mass propagate the species to address the problem. Somatic embryogenesis (SE) could produce higher number of propagates. Beside, SE is studied to understand similar process of zygotic embryogenesis. The purpose of this research was to look for cellular and molecular markers during the early events of SE. Explants of D. burmannii and D. tokaiensis were subcultured on a medium supplemented with thidiazuron to induce SE. Explants were sampled based on different incubation period where day-0 sampling served as negative control. Major events that occurred from the transition of induced cells into somatic embryo, and up to globular structure were investigated using histology. Specific primers targeting EF1 and GAPDH were designed from previous isolated sequences from D. tokaiensis. Degenerate primers were also designed from downloaded database sequences. RT-PCR was performed using the designed specific and degenerate primers followed by sequence analysis. Isolation of SE induced cells from their surrounding was observed. Early evets leading to the formation of globular structures in epidermis cells reconfirmed a previous study, which was documented alongside some new findings elaborated in the Results section. SE from induced mesophyll cells proposed previously was documented in this study. Specific primers targeting EF1 and GAPDH genes successfully amplified their target sequence and could be used for quantitative PCR (qPCR) in future. ACT and SERK1 sequences were isolated and could be used for designing qPCR specific primers for detection of SE in D. tokaiensis. SERK1 gene could be used for early detection of SE while ACT, EF1 and GAPDH could be used as a normalisation in qPCR. Findings obtained in this research facilitate deeper understanding of early development of SE and SE regeneration pathway could serve as a reference to provide understanding in other plant species.